Innovative carboxylic acid waterproofing admixture for self-sealing watertight concretes. (20th May 2018) - Coppola, L.; Coffetti, D.; Crotti, E.
Highlights: Performances of innovative self-sealing admixture were investigated. Fumaric acid-based waterproofing admixture improves concrete watertightness. Self-sealing ability was confirmed on 400 μm width cracks. Abstract: The present paper evaluates the performances of an innovative carboxylic acid-based admixture to improve concrete watertightness and self-sealing ability of the cement matrix. Results indicate that fumaric acid-based waterproofing admixture improves concrete watertightness. In particular, addition of 1% by cement mass of the carboxylic polymer causes a reduction in the water penetration under pressure of 7-day wet cured concrete by 50% compared to that of the corresponding reference concrete. The ability to seal cracks (400 μm width) due to plastic shrinkage was also confirmed by Karsten tubes tests, optical microscopy and SEM observations on cracked and sound concrete slabs.